Sebuah Laporan Kasus Subdural Hematom: Subdural Hematom: Sebuah Laporan Kasus - Anggela Anggela; Frecilia Afrida; Fitriyani Fitriyani (CV. Jasa Sukses Abadi, 2026)
Subdural hematoma (SDH) is a neurological disorder characterized by the accumulation of blood beneath the dura mater. Its incidence ranges from 1.7 to 20.6 cases per 100,000 population annually, with a higher prevalence observed in the elderly. Known risk factors associated with SDH include traumatic brain injury such as traffic accidents, advanced age, alcohol consumption, anticoagulant use, and various medical conditions such as epilepsy, hemophilia, hydrocephalus, cerebral aneurysm, and malignancies. A 19-year-old female patient, Ms. ZA, presented to the Emergency Department of Abdul Moeloek Regional General Hospital (RSUDAM) with complaints of persistent headaches radiating to the posterior neck region, which significantly interfered with daily activities. The patient had a history of a traffic accident two weeks prior to admission. According to her family, she lost consciousness for approximately two hours and experienced hematemesis following the incident. There were no reported symptoms of limb weakness, epistaxis, otorrhagia, or seizures. On physical and neurological examination, no abnormalities were identified. However, a cranial CT scan revealed a subacute subdural hematoma in the left frontoparietal region with a thickness of 0.47 cm. The patient was managed conservatively with both pharmacological and planned surgical interventions. Medical therapy included intravenous Mannitol titration dose, Paracetamol 3x750 mg, Ranitidine 2x1 ampoule, along with oral supplementation of vitamin B12 and folic acid, each administered twice daily. Surgical management involved a planned burr hole drainage procedure by the attending neurosurgeon.